PELANGGARAN PRINSIP KERJASAMA DAN DAMPAKNYA DALAM NOVEL TOTTO-CHAN KARYATETSUKO KUROYANAGI - Suci Rahmawati; Mangatur Sinaga; Hermandra ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This study aims to describe the principles infraction of cooperation are contained in Totto-chan novel by Tetsuko Kuroyanagi. The principles of cooperation in a conversation that is maxim of quantity, maxim of quality, maxim of relevancy, and maxim of the way. Basides that, this study also talked about the effect of the principles infraction of the conversation between the characters in the novel. This study is a quantitative research with design of descriptive. The result of research in the form of the classification of the principles infraction of cooperation and its effect in Totto-chan novel by Tetsuko Kuroyanagi. The result of this research is a form of documentasion of the principles infraction of the principles infraction in the novel.Key words: the principles of cooperation, the infraction of the principles of cooperation, and the effect of the principle infraction of cooperation.